(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
E-commerce in trade companies during the course of the pandemic crisis has become more than a technology; it includes a whole range of activities such as business processes, business organization, communication, customer relationship management, the E-sales orientation and business progress through the Information and Communication technologies. The consequences of the pandemic COVID-19 are reflected on the various spheres of social life, including the businesses of the companies. New strategies and techniques in business have positively contributed to the survival of trading companies on the market in the new situation. Therefore, trading companies were forced to adjust their way of working, doing business and maintaining contacts with the customers and suppliers in the new situation. E-commerce in trading companies has become much more than the E-sales. Digitalising business leads to the implementation of E-commerce of the supply chain management that leads to speeding up and maintaining of the business processes. Due to rapid technological changes, E-commerce needs to follow new trends on the Information and Communication technologies market in order to remain effective. E-commerce can also help to organize communication processes. Online sales in the situation of the pandemic crisis have proven to be an effective sales method with which trading companies can maintain their sales in contactless customer relations. With the E-commerce can be improved all the company’s business relations by the introduction of opportunities that it provides in business, by building architecture of E-commerce and by implementation of applications for business enterprises taking into account the potential costs and benefits of introducing this kind of business. However, with the introduction of E-commerce, both of the marketing strategies and the market expansions can be improved. In the paper are listed and analysed changes in the trade operations of the two companies due to the pandemic crisis; one deals with the sale of agricultural machinery and the other with the sale of food products: at this point we examine and compares the differences in the business processes management with the customers and suppliers in the normal way of doing business also in the new occasions, that is the consequential business adjustment in the course of pandemic.